Teaching English literature at IIUM: Islamic perspectives on selected twentieth-century texts - Hasan, Md. Mahmudul (2015)
Among the humanities and social sciences disciplines, English literature is perhaps the most contentious subject as it carries subtle ideological and cultural impacts and significance. Right from the beginning of its introduction in British India and elsewhere, the most prominent consideration was its inherent worth as a carrier of values and norms. Under the surface of its seemingly value-neutral tag, English literature promotes ideas, beliefs and philosophies which can potentially influence its learners and practitioners. Based on this theoretical premise, this paper will establish the necessity of critically evaluating English literary texts in a Muslim setting and of bringing in Islamic perspectives in pedagogical practices at such an Islamic university as International Islamic University Malaysia (IIUM). It will discuss few twentieth-century English literary works and suggest ways of looking at them from Islamic viewpoint.